Research on Shift Control of Two-gear Dual Clutch Transmission in Pure Electric Vehicles - Qinglin Dai; Zhongli Zhang; Yong Chen; Yi Wang; Sen Xiao (Jixie chuandong)
Pure electric vehicle two-gear dry dual clutch automatic transmission completes the shift through the control of two clutches engagement and separation. Since the friction coefficient of clutch changes with temperature， the parameter adaptive method is used to estimate the friction coefficient online in real time. According to the shifting dynamics model， a backstepping controller based on the extended state observer is designed， and the shifting process is transformed into speed tracking problem by giving the target speed of the motor and the first gear clutch disk. Simulation and hardware-in-the-loop verify that the controller can effectively ensure the shift quality of automatic transmission under the condition of external interference， and has good robustness.